Interpersonal communication: roles, rules, strategies and games - Smith, Dennis R.; Williamson, L. Keith (Subuque: Wm. C. brown publishers, 1977)
Contents: part 1. transactional model of interpersonal communication. part 2. primary message systems. part 3. patterns of interpersonal communication.
Glossary p. 317 - 324 index p. 325 - 331.
Keywords: Comunicación Interpersonal